From ancient Rome to colonial Mexico: religious globalization in the context of empire - Wright-Carr, David Charles, editor; Simón, Francisco Marco, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2023)
From Ancient Rome to Colonial Mexico compares the Christianization of the Roman Empire with the evangelization of Mesoamerica. With the analysis of empire and globalization and a postcolonial perspective on religion, the book proposes the method of "analytical comparison" to conceptualize affinities and differences between geographies.--Provided by publisher.
Ritual mediation on the middle ground: Rome and New Spain compared / Greg Woolf -- A long way to become Christian: Romans, Hungarians, and the Nahua / György Németh -- Human sacrifice and the religion of the other: barbarians, pagans and Aztecs / Francisco Marco Simón -- The Aztec sun and its Mesoamerican milieu from a classical Mediterranean perspective / Lorenzo Pérez Yarza -- Donkeys and hares: the enemy warrior in the early European Chronicles of the Conquest / Paolo Taviani -- Cultural persistence and appropriation in the Huamantla map / David Charles Wright-Carr -- Comparison and the Franciscan construction of Mesoamerican polytheism through Augustine of Hippo's De Civitate Dei / Sergio Botta -- Bernardino de Sahagún on Nahua astrology and divination: Greco-Roman traditions, Christian disapproval and ambiguity, and Mesoamerican practices / Guilhem Olivier -- A version of the millennial Kingdom in the Portería of the Franciscan Convent in Cholula, México / María Celia Fontana Calvo -- Smoking stones and smoking mirrors: the limits of antiquarianism in New Spain / Martin Devecka.
Keywords: Globalization -- Religious aspects; Globalization -- Social aspects -- Rome; Globalization -- Social aspects -- New Spain; Imperialism -- Religious aspects; Acculturation -- Religious aspects; New Spain -- History -- Religious life and customs; Rome -- History -- Religious life and customs